2015
DOI: 10.1007/s00773-015-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

A study on slamming pressure on a flat stiffened plate considering fluid–structure interaction

Abstract: Normally, the design slamming pressure on the bottomof a semi-submersible-type floating rig is determined in a simple way using the relative speed obtained from an air-gap analysis. However, few studies have taken a thorough, robust, and deep-background approach to the estimation of design pressure. To investigate the slamming pressure on the bottom of a semi-submersible rig, a simplified deformable stiffened plate of a zero-degree deadrise angle is simulated using the nonlinear FEM software LS-DYNA, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Souli and Benson [9] highlighted the capability of penalty coupling algorithms by simulating a 2D wedge with 10 deadrise angle and demonstrated that the local peak pressure is sensitive to the penalty factor. Cheon et al [10] used the ALE algorithm to simulate the water entry problem of a deformable flat stiffened panel. They examined the effects of mesh sensitivity, structural flexibility, and penalty factors on the results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Souli and Benson [9] highlighted the capability of penalty coupling algorithms by simulating a 2D wedge with 10 deadrise angle and demonstrated that the local peak pressure is sensitive to the penalty factor. Cheon et al [10] used the ALE algorithm to simulate the water entry problem of a deformable flat stiffened panel. They examined the effects of mesh sensitivity, structural flexibility, and penalty factors on the results.…”
Section: Introductionmentioning
confidence: 99%
“…They examined the effects of mesh sensitivity, structural flexibility, and penalty factors on the results. The effect of damping factors on the impact loads was not considered in their study [10]. A study of the numerical uncertainty caused by discretization for the ALE method in predicting impact-induced loads on rigid and elastic flat plates was conducted by Wang et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth highlighting how, in the recent past, due to the increased computational power availability, many efforts have been devoted in defining models for the contemporary solution of both fluid and solid motion/deformation [19]. In naval application, this reflects always increasing attention to the analysis of impulsive loads due to slamming of rigid/deformable wedges/obstacles [20,21]. With respect to lattice Boltzmann method (LBM), many studies have already been carried out considering both rigid and flexible obstacles interacting with fluid flows [22].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, aero-elasticity couples a stiff structure with a light and possibly compressible fluid [39], while in bio-engineering a very flexible structure and an incompressible fluid with comparable densities are coupled [13]. In naval or marine engineering structures interact with a free surface flows and are subject to a slamming pressure impulsive load [12,[40][41][42].…”
Section: Introductionmentioning
confidence: 99%